2017
DOI: 10.20884/1.sb.2017.4.2.423
|View full text |Cite
|
Sign up to set email alerts
|

METODE EKSTRAKSI DNA CABAI (<em>Capsicum annuum</em> L.) MENGGUNAKAN MODIFIKASI BUFFER CTAB (CETHYL TRIMETHYL AMMONIUM BROMIDE) TANPA NITROGEN CAIR

Abstract: A B S T R A C TChili pepper is an agricultural commodity having high economic value. The production and supply of chili pepper frequently did not match the increased demand; it caused the market price fluctuated. It is important to create new varieties of chili pepper with high production trait to overcome the scarcity. Therefore the plant breeding activities for chili pepper should be done intensively in both conventional and molecular-based to obtain varieties of chili pepper with expected qualities. In mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This was due to the extracted samples coming from different sources there was meat and meatballs and sausage. According to the KapaBiosystem (2014) recommendation cited by Nugroho et al (2017), the template DNA concentration needed for PCR activities ranged from 10-100 µg/mL whereas according to Maryam (2014) the optimal concentration in PCR amplification at 30 cycles to produce thick bands was a 50 µg/mL concentration both in beef comparison, pork, beef meatball samples and pork meatball samples. In this study showed that the concentration of DNA in beef and pork samples was very high, namely 558.90 and 610.65 µg/mL, because the extracted sample was a fresh meat without any mixture material.…”
Section: Resultsmentioning
confidence: 99%
“…This was due to the extracted samples coming from different sources there was meat and meatballs and sausage. According to the KapaBiosystem (2014) recommendation cited by Nugroho et al (2017), the template DNA concentration needed for PCR activities ranged from 10-100 µg/mL whereas according to Maryam (2014) the optimal concentration in PCR amplification at 30 cycles to produce thick bands was a 50 µg/mL concentration both in beef comparison, pork, beef meatball samples and pork meatball samples. In this study showed that the concentration of DNA in beef and pork samples was very high, namely 558.90 and 610.65 µg/mL, because the extracted sample was a fresh meat without any mixture material.…”
Section: Resultsmentioning
confidence: 99%
“…DNA extraction was carried out using the Cetyl Trimethyl Ammonium Bromide (CTAB) method [19], which was modified by adding 2% PVP (Polyvinylpyrrolidone) and β-mercaptoethanol. The addition of PVP is carried out to reduce polyphenolic compounds that can bind to DNA, while the compound βmercaptoethanol was added to the extraction buffer to degrade proteins in the sample so that pure and high DNA results will be obtained [20].…”
Section: Genomic Dna Extractionmentioning
confidence: 99%
“…The homogenized DNA solution and DNA Ladder were injected into the well of a 1% agarose gel (0.5 grams of agarose, 50 ml of 1x TBE buffer, and 5 µl of fluorosafe), which was submerged in 1x TBE buffer solution and ran at 50 volts for one hour. After the electrophoresis process was complete, the agarose gel was transilluminated under a UV transilluminator [20]. The purity of the DNA solution was determined if there was a single genomic DNA band and there was no smear on the agarose gel resulting from electrophoresis [17].…”
Section: Visualization and Quantification Of Dnamentioning
confidence: 99%
“…Therefore, DNA isolates from meat samples were tested quantitatively, as shown in Table 2. The concentration of DNA templates required for the PCR process ranges from 10 to 100 ng/μl (Nugroho et al, 2017). It is the total concentration of DNA in the PCR mix.…”
Section: Dna Isolation and Quantitative Measurementmentioning
confidence: 99%